2006
DOI: 10.1002/app.24908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clay dispersion on the foam morphology of LDPE/clay nanocomposites

Abstract: Intercalated and exfoliated low-density polyethylene (LDPE)/clay nanocomposites were prepared by melt blending with and without a maleated polyethylene (PE-g-MAn) as the coupling agent. Their morphology was examined and confirmed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The effects of clay content and dispersion on the cell morphology of nanocomposite foams during extrusion foaming process were also thoroughly investigated, especially with a small amount of clay of 0.05-1.0 wt%. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
80
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 24 publications
3
80
2
3
Order By: Relevance
“…The effect of adding a compatibilizer agent has also been carefully analyzed. Lee et al [16] and Seraji and co-workers [17] performed similar studies using low density polyethylene (LDPE) as polymeric matrix and montmorillonite (MMT) as filler. They concluded that the addition of a compatibilizer led to a clay exfoliation and only in this case, the nucleation effect induced by MMT was effective.…”
Section: Introductionmentioning
confidence: 97%
“…The effect of adding a compatibilizer agent has also been carefully analyzed. Lee et al [16] and Seraji and co-workers [17] performed similar studies using low density polyethylene (LDPE) as polymeric matrix and montmorillonite (MMT) as filler. They concluded that the addition of a compatibilizer led to a clay exfoliation and only in this case, the nucleation effect induced by MMT was effective.…”
Section: Introductionmentioning
confidence: 97%
“…To seek this aim, different continuous and discontinuous process variants have been developed to prepare microcellular foam morphologies from glassy polymers [1,3,4]. Similarly, there are some reports about clay reinforced nanocomposite foams based on semicrystalline polymers [5][6][7][8]. Moreover, microcellular foaming process is one of the techniques that have been studied for this purpose [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…12 It is well known that cell density and cell size are the most important characteristics of microcellular foams, and the majority of the studies of microcellular foams have been focused on increasing cell density and decreasing cell size. [15][16][17] More recently, the incorporation of nanoscaled additives has been considered to enhance cell nucleation and produce more bubbles with a finer morphology. [16][17][18][19][20][21] Nanocellular foams have also been achieved in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] More recently, the incorporation of nanoscaled additives has been considered to enhance cell nucleation and produce more bubbles with a finer morphology. [16][17][18][19][20][21] Nanocellular foams have also been achieved in some cases. 22,23 Furthermore, the addition of nanofillers to polymers cause remarkable improvement in their properties, such as the modulus, strength, thermal stability and gas permeability resistance, compared with non-filled and microfilled ones.…”
Section: Introductionmentioning
confidence: 99%